Implementation of Occupational Safety and Health Management System in the Education Sector - Fitrijaningsih, Fitrijaningsih; Purnamawati, Dewi; Srisantyorini, Triana; Baktiansyah, Abdul; Triyono, Agus (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The frequency of work accidents, occupational illness, and natural disasters that influence schools and universities requires the implementation of occupational safety and health not only in the industrial sector, but also in the education sector. This study aimed to implement the Occupational Safety and Health Management System (hereinafter OSHMS) at the Public Health Faculty University of Muhammadiyah Jakarta as part of an effort to protect all academic community, contractors, guests, and visitors from work accidents and occupational diseases. Method: This study was operational research that employs an implementation framework, which involves the entire population in the faculty as the research sample. Data was analyzed descriptively both qualitative and quantitative. Result: OSHMS is successfully implemented with the stipulation of several policies at the Public Health Faculty University of Muhammadiyah Jakarta through the Dean's Decree Number 05 of 2022 concerning Determination of Occupational Safety and Health Policies, the formation of an occupational safety and health committee through the Dean's Decree Number 04 of 2022, implementation of OSHMS socialization, and installation of signs related to safety and health in the workplace. Conclusion: The implementation strategy carried out through the stages of exploration, installation, initial implementation, and sustainability was successfully used as a guide in realizing the implementation of OSHMS at the Public Health Faculty University of Muhammadiyah Jakarta.